Beauty in the broken places : a memoir of love, faith, and resilience - Pataki, Allison (Random House, 2018)
"A deeply moving memoir about two lives that were changed in the blink of an eye, and the love that helped them rewrite their future. Five months pregnant, on a flight to their "babymoon," Allison Pataki turned to her husband when he asked if his eye looked strange, and watched him suddenly lose consciousness. After an emergency landing, she discovered that Dave--a healthy thirty-year-old athlete and surgical resident--had suffered a rare and life-threatening stroke. Next thing Allison knew, she was sitting alone in the ER in Fargo, North Dakota, waiting to hear if her husband would survive the night. When Dave woke up, he could not carry memories from hour to hour, much less from one day to the next. Allison lost the Dave she knew and loved when he lost consciousness on the plane. Within a few months, she found herself caring for both a newborn and a sick husband, struggling with the fear of what was to come. As a way to make sense of the pain and chaos of their new reality, Allison started to write daily letters to Dave. Not only would she work to make sense of the unfathomable experiences unfolding around her, but her letters would provide Dave with the memories he could not make on his own. She was writing to preserve their past, protect their present, and fight for their future. Those letters became the foundation for this beautiful, intimate memoir. And in the process, she fell in love with her husband all over again. This is a manifesto for living, an ultimately uplifting story about the transformative power of faith and resilience. It's a tale of a husband's turbulent road to recovery, the shifting nature of marriage, and the struggle of loving through pain and finding joy in the broken places"--